Inhibition of Pathological Retinal Neovascularization by a Small Peptide Derived from Human Tissue-Type Plasminogen Kringle 2 - Sun, Qian; Shen, Yinchen; Su, Li; Xu, Xun (Frontiers in Pharmacology, 2020)
Retinal neovascularization is a hallmark pathological process of numerous ocular diseases which comprise the most common causes of blindness and affect millions of people from infants to the elderly. Compared to large proteins, small peptides have advantages for therapeutic application in ocular diseases, especially for retinal diseases. In this study, we investigated a small peptide derived from human tissue-type plasminogen kringle 2 (t-PA kringle 2), named TKII-12, and investigated the effect of TKII-12 on various aspects of vascular endothelial growth factor (VEGF)-induced angiogenesis in vitro and in vivo. Our results showed that TKII-12 effectively inhibited VEGF-induced human retinal microvascular endothelial cell proliferation, migration and tube formation on Matrigel dose-dependently as well as sequence-dependently. TKII-12 inhibited VEGF-induced focal adhesion kinase (FAK), extracellular signal-regulated kinase (ERK), and p38 mitogen-activated protein kinase (MAPK) phosphorylation and decreased the formation of actin stress fibers and focal adhesions in vascular endothelial cells. Moreover, TKII-12 effectively inhibited retinal neovascularization in a mouse oxygen-induced retinopathy (OIR) model. Our study demonstrated that TKII-12 could effectively inhibit retinal angiogenesis in vitro and in vivo by interfering with the phosphorylation of FAK, ERK, and p38 MAPK and eliminating the formation of focal adhesion complexes and the organization of actin stress fibers. TKII-12 can serve as a prototype for retinal angiogenesis inhibitory drug development.